Comparative evaluation of antimicrobial substantivity of different concentrations of chlorhexidine as a root canal irrigant: An in vitro study - Abhishek Mahendra; Monika Koul; Vinod Upadhyay; Rahul Dwivedi (Journal of Oral Biology and Craniofacial Research)
Introduction: The aim of this in vitro study was to evaluate and compare the antimicrobial substantivity of different concentrations of chlorohexidine as root canal irrigant by microbiological assay using mitis salivarius bacitracin streptomycin, MSBS agar plate. Methods: Extracted single rooted permanent human teeth were selected as samples and randomly divided into four groups (three experimental, one control). The samples of the three experimental groups used different concentration of chlorhexidine, CHX (0.1%, 1% and 2%), deionized water used as an irrigant served as control. In each group the apices of teeth were sealed with composite and mounted on plaster blocks. Root canals were prepared using step back technique and enlarged upto no 80. With each change in the file size the corresponding irrigant was used and final irrigation was done with deionized water. Samples were taken with paper points at 12 h, 1 day, 2 days and 3 days respectively and stored in sterile phials which were then arranged on MSBS agar plates for microbiological assay. Results and conclusion: Results were analysed by ANOVA and Tukey's HSD test showed that antibacterial substantivity of 2% CHX was best followed by 1% CHX and 0.1% CHX in decreasing order respectively.